(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Presently in India we have more than 1200 law colleges and center of legal education other than the 23 National law Universities importing of legal education under 3 years and 5 years integrated programs, but in the context of present scenario the exiting patters of importing of legal education specially by the law colleges and center or department of legal education , is not perfectly all right to cater the need of law students as well the judiciary then what are the lacunas is existed in our legal education system and how can these be eliminated, that reason has been elaborately discussed in this Article